Class-Based Affirmative Action: Creating a New Model of Diversity in Higher Education - Neil Goldsmith (Washington University Journal of Law & Policy, 2010)
This Note proposes that class-based affirmative action policies should be further implemented in university admissions. While the benefits of class-based policies are clear, most institutions have been hesitant to implement such initiatives for fear of subsequently reducing minority enrollment. Although class-based plans have the potential to limit minorities‘ participation in higher education, if the proper variables are taken into account by admissions offices, these plans would provide a much needed boost to both minorities and disadvantaged white applicants, creating greater socioeconomic diversity while maintaining racial diversity. Thus, this Note concludes that the implementation of class-based policies would not represent the end of race-based affirmative action. Rather, these policies would represent an important modification of race-based policies to achieve the same basic diversity goals while not sacrificing opportunities for well-qualified white students. Part I of this Note will discuss the history of both race-based affirmative action and class-based affirmative action, with a focus on the seminal case law and current public policy debate. Part II will examine the legality of class-based affirmative action policies, and explain why such policies offer a significant advantage over strictly racial policies. Finally, in Part III, this Note will identify the characteristics of an effective class-based affirmative action policy, and propose specific factors and metrics universities should consider when designing an appropriate plan.
Keywords: Universities & amp; colleges – Admission; Affirmative action programs in education; Race discrimination; Social classes; Equal rights; Equal education